Reuse of shrimp farm wastewater as growth medium for marine microalgae isolated from Red Sea – Jeddah. (10th October 2018) - Malibari, Raghdah; Sayegh, Fotoon; Elazzazy, Ahmed M.; Baeshen, Mohamed N.; Dourou, Marianna; Aggelis, George
Abstract: Microalgae can grow effectively on various wastewaters, including those generated in aquaculture as a result of operation of hatcheries and farming systems. These organisms are able to remove pollutants from their growth environment, while the biomass produced can be further exploited. Such biomass contains lipids rich in polyunsaturated fatty acids and other substantial nutrients and can be used as a live feed in shrimp farming or in fisheries, i.e. as live feed for zooplankton or as fish feed supplement after enzymatic and/or chemical treatment. In the current work, a shrimp farm wastewater (SFW) with high nutrient (P, N) concentrations was used as growth medium for six newly isolated marine microalgae strains from Saudi Arabian coastal waters, including Chlorella sp., Dunaliella sp., Nannochloropsis sp., Navicula sp. (two strains) and Tetraselmis sp.. The growth yields and kinetics parameters were compared to those obtained in synthetic f/2 medium. Among these strains, Navicula sp. (both strains) and Tetraselmis sp. were able to grow well on SFW, producing high lipid quantities (especially Navicula sp. 1) containing polyunsaturated fatty acids, including eicosapentaenoic acid. However, microalgae lipids produced in SFW medium were in general more saturated than those produced in f/2 medium. It seems that several desaturases, of both the C16 and C18 group, and probably the C16:0 elongase, were inhibited in SFW medium modifying accordingly the fatty acid profile. Considering the overall physiological behavior of the strains, including biomass yields and fatty acid composition, we conclude that SFW can be valorized in a sustainable way for microalgae production in fisheries. Graphical abstract: Image 1 Highlights: The shrimp farm wastewater (SFW) can be considered as growth medium for microalgae. Six newly isolated strains were cultivated in SFW. Biomass and lipid yields in SFW were comparable to those obtained in f/2 medium. Desaturases involved in polyunsaturated fatty acid synthesis maybe inhibited in SFW medium.